Pengelolaan Administrasi Madrasah Tsanawiyah Al-Ihsan dalam Meningkatkan Kualitas Pendidikan Madrasah - Julaiha Julaiha; Siti Jumrah; Adiyono Adiyono (Journal on Education, 2023)
Our goal in this research is to find out how administration is managed at Mts Al-Ihsan Tanah Grogot, how to improve the quality of madrasas. This research uses qualitative. The data collection technique that we use is observation, documentation and interviews. The results obtained are that the administrative management at Mts Al-Ihsan Tanah Grogot is going well in improving the quality of madrasas. The administration of the Madrasah curriculum has been going well, as evidenced by the students who successfully pass one hundred percent every year and Accreditation A. The quality can be seen from the curriculum, educators, and education staff. This research has a relationship between supervisors and Madrasah involvement. To study administrative management at MTs Al-Ihsan Tanah Grogot in improving the quality of Madrasas.